Aplikasi Pengolahan Data Permintaan dan Pengeluaran Material Teknik di Perusahaan Umum Daerah Tirta Hidayah Kota Bengkulu Berbasis Web - Yuza Reswan; Muntahanah Muntahanah; Eka Sahputra; Yolan Pagestu (Jurnal Media Infotama, 2024)
Tirta Hidayah, Bengkulu City, distributes water to customers using pipes and engineering materials designed to work properly. However, this does not always run smoothly, because technical and non-technical problems often occur. To carry out the process of handling and correcting problems that occur in the field, each department must order goods in the warehouse. However, the problem is that the location between offices is quite far and the administration is quite long, making the demand and expenditure of goods not optimal and has an impact on customer service. Of course, this situation can hamper service to customers, because the currently available applications can only be accessed offline. Therefore, the author is interested in creating a web-based application for the PHP programming language and Mysql database. The system development was carried out using the waterfall SDLC model, with the result that the application for processing data on demand and expenditure of engineering materials with a web-based system at the Tirta Hidayah Regional Public Company, Bengkulu City, which was built has been running well, and this application is useful and helps the Service Unit (Processing, Transmission and Distribution Installation, New Installation) and Warehouse Sub Division and Tirta Hidayah General Section of Bengkulu City in the process of requesting and releasing technical materials to be more effective and efficient